Case study report : supporting school-university pathways for refugee students' access and participation in tertiary education. - Naidoo, Loshini; Wilkinson, Jane; Langat, Kiprono; Adoniou, Misty; Cunneen, Rachel; Bolger, Dawn (University of Western Sydney, 2014)
This report examines the barriers and challenges faced by refugee background students transitioning from Australian secondary school to university. As part of a larger Office for Learning and Teaching (OLT) funded cross-institutional study it focuses on three main regions - Greater Western Sydney, Wagga Wagga and Albury (regional NSW); and Canberra (ACT). Data obtained from the interviews with students revealed that the various complex prior life and educational experiences of refugee background students present a number of significant barriers and challenges to their successful transition from secondary school to university. Many of the refugee background students interviewed had high aspirations for educational attainment and a strong desire to succeed academically. Successful transition to tertiary education was inextricably linked to positive interpersonal relationships with peers, teachers, support staff and the wider community combined with the ability to navigate the Australian educational system. Specifically, the students highlighted the challenges of forced migration, interrupted schooling and significant differences in teaching pedagogy as barriers to educational achievement. [p,5-6, ed]